Role Ambiguity, Workload, and Work Motivation Influenced the Turnover Intention among Employees at Mother and child hospital - Palili, Mohammad Ridwan; Hasyim, Hasyim; Pamungkas, Rian Adi (Alta Dharma Publisher, 2023)
Background: Human resources play an essential role in achieving the success and goals of the hospital. Thereby, to connect all scopes of human resources, there needs to be good management. Objective: This study aims to analyze the effect of role ambiguity and workload and work motivation on employee turnover intention at Mother and Child Vitalaya Hospital. Method: A correlation study with a cross-sectional approach was applied in this study. Result: Multiple linear regression tests show that the coefficient of determination R square is 0.735. This indicates that role ambiguity, workload, and work motivation simultaneously contribute 74% to turnover intention. However, partially only work motivation influences employee turnover intention at Mother and Child Vitalaya Hospital. Conclusion: role ambiguity and workload were strong predictors of employee turnover intention. Recommendation: The human resource unit must consider those factors to prevent employee turnover. Further studies need to test other elements with a broad population to ensure the role of factors in avoiding turnover intention